Real-World Treatment Patterns and Healthcare Resource Utilization in Patients Prescribed Benztropine: A Claims Analysis From 2017-2020. (April 2023) - Chepke, Craig; Cicero, Samantha; Giraldo, Erika; Hull, Michael; Coyle, Katharine; Yeaw, Jason; Bron, Morgan
Abstract: Introduction: We sought to examine real-world treatment patterns and healthcare resource utilization (HCRU) for patients receiving an antipsychotic (AP) and subsequently prescribed benztropine. Methods: A retrospective analysis was conducted among patients with evidence of benztropine initiation using claims data from IQVIA's New Data Warehouse from January 2017–March 2020. Patients were indexed on the date of first pharmacy claim for benztropine and had continuous enrollment in the 6 months prior (pre-index) and minimum 12 months post-index date, up to 24 months. Patients also had ≥1 pharmacy claim for an AP either pre-index or on the index date. Results: A total of 112, 542 patients were included; 59% were female with mean age of 46 years. The most common comorbidities were bipolar disorder (BD; 28.3%), schizophrenia (SCZ; 28.3%), and depression (26.3%). Over half of the cohort (54.1%) had ≥2 comorbid conditions. Nearly 20% of patients had ≥20 medications (median 10–14) and medications with anticholinergic (AC) properties were used by 87.9%. Approximately 80% of patients had mild AC burden at baseline (using AC burden calculator). The median number of benztropine prescription fills was 5 with treatment duration <3 months in 44.3% of patients and <6 months in 61.7%. All-cause mean healthcare costs in the 12-month cohort (24-month cohort) were 11, 755 (23, 128), mean costs for pharmacy were 9, 229 (18, 148), and mean costs for inpatient stays were 34, 669 (41, 280). Emergency room (ER) visits occurred in 47.3% and physician office visits in 78.9% of the cohort. In patients with available inpatient 12-month data (n=33, 717), inpatient stays occurred in 4.0% (13.3% when extrapolated to total cohort). In patients with 24-month data (n=73, 836), ER visits occurred in 61% of the cohort and inpatient stays in 6.6% (21.9% when extrapolated to the total cohort). Multivariate analyses showed baseline SCZ was associated with a significantly increased risk of ER visit of 30% and inpatient stay of 50%. Similarly, substance abuse was associated with an increased risk of ER visit of 85% and inpatient stay of about 40%. Other significant associations with ER visits included falls/accidents at baseline (148% increased risk), abnormal movement disorders (38% increased risk), and orthostatic hypotension (38% increased risk). Conclusions: In this real-world analysis of patients initiating benztropine, polypharmacy and AC burden were frequently observed. BD, SCZ, and depression were the most common comorbidities. Healthcare costs and HCRU were high for the entire cohort; inpatient stays contributed to high costs. Baseline SCZ, falls/accidents (ER only), and substance abuse were significantly associated with ER and inpatient admissions. The comorbidity and medication profiles of this cohort may have influenced the high healthcare costs and HCRU observed in the study. Funding: Neurocrine Biosciences, Inc.